Compensatory enlargement of human coronary arteries identified by magnetic resonance imaging - Bertini,P.J. (2005)
The aim of the present study was to evaluate the role of magnetic resonance imaging (MRI) for the non-invasive detection of coronary abnormalities and specifically the remodeling process in patients with coronary artery disease (CAD). MRI was performed in 10 control healthy subjects and 26 patients with angiographically proven CAD of the right coronary (RCA) or left anterior descending (LAD) artery; 23 patients were within two months of acute coronary syndromes, and 3 had stable angina with a positive test for ischemia. Wall thickness (WT), vessel wall area (VWA), total vessel area (TVA), and luminal area (LA) were measured. There were significant increases in WT (mean ± SEM, RCA: 2.62 ± 0.75 vs 0.53 ± 0.15 mm; LAD: 2.21 ± 0.69 vs 0.62 ± 0.24 mm) and in VWA (RCA: 30.96 ± 17.57 vs 2.1 ± 1.2 mm²; LAD: 19.53 ± 7.25 vs 3.6 ± 2.0 mm²) patients compared to controls (P < 0.001 for each variable). TVA values were also greater in patients compared to controls (RCA: 44.56 ± 21.87 vs 12.3 ± 4.2 mm²; LAD: 31.89 ± 11.31 vs 17.0 ± 6.2 mm²; P < 0.001). In contrast, the LA did not differ between patients and controls for RCA or LAD. When the LA was adjusted for vessel size using the LA/TVA ratio, a significant difference was found: 0.33 ± 0.16 in patients vs 0.82 ± 0.09 in controls (RCA) and 0.38 ± 0.13 vs 0.78 ± 0.06 (LAD) (P < 0.001). As opposed to normal controls, positive remodeling was present in all patients with CAD, as indicated by larger VWA. We conclude that MRI detected vessel wall abnormalities and was an effective tool for the noninvasive evaluation of the atherosclerotic process and coronary vessel wall modifications, including positive remodeling that frequently occurs in patients with acute coronary syndromes.